2018
DOI: 10.1055/a-0661-0341
|View full text |Cite
|
Sign up to set email alerts
|

The 3PAs: An Update on the Association of Pheochromocytomas, Paragangliomas, and Pituitary Tumors

Abstract: Supplementary material for this article is available online at http://www.thieme-connect.de/products. ABStr AC tPituitary adenomas (PA) and pheochromocytomas/paragangliomas (PHEO/PGL) are rare tumors. Although they may co-exist by coincidence, there is mounting evidence that genes predisposing in PHEO/PGL development, may play a role in pituitary tumorigenesis. In 2012, we described a GH-secreting PA caused by an SDHD mutation in a patient with familial PGLs and found loss of heterozygosity at the SDHD locus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 113 publications
1
35
0
12
Order By: Relevance
“…Unselected cohorts of PAs have relatively low rates of SDH deficiency and unpublished data from our centre has shown 1 case in 150 unselected surgical PA cases (0.7%). This is in keeping with published data suggesting a prevalence of 0.3%‐1.8% in unselected PA cases 43,44 . A recent study reviewing the frequency of germline genetic mutations in a select cohort of patients with a history of PC, PGL and pituitary tumours, demonstrated that SDHx mutations were the most common germline mutation observed (19/82 cases (23%)) 44 …”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Unselected cohorts of PAs have relatively low rates of SDH deficiency and unpublished data from our centre has shown 1 case in 150 unselected surgical PA cases (0.7%). This is in keeping with published data suggesting a prevalence of 0.3%‐1.8% in unselected PA cases 43,44 . A recent study reviewing the frequency of germline genetic mutations in a select cohort of patients with a history of PC, PGL and pituitary tumours, demonstrated that SDHx mutations were the most common germline mutation observed (19/82 cases (23%)) 44 …”
Section: Resultssupporting
confidence: 88%
“…Vacuolated clear cytoplasm has been documented as a characteristic histological hallmark of SDH‐deficient PA 45 and it has been hypothesized these may be by‐products of autophagy of abnormal mitochondria 44 (Figure 1). Definitive description of the SDH‐deficient PA clinical phenotype is difficult given the low number of reported cases thus far, but the majority of the reported PAs are of PIT‐1 lineage (lactotropinomas or somatotropinomas) although isolated reports of silent gonadotroph adenomas and corticotropinomas have been documented 44 . There is no clear genotype‐phenotype correlation for SDH‐deficient PA and mutations in all four SDHx subunit genes have been reported to associate with the presence of these tumours 44 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The article follows a number of recent articles in our journal on the treatment and genetics of pituitary tumors; some are listed here as examples [4][5][6][7].…”
mentioning
confidence: 99%
“…One further syndromic situation of growing interest is the potential for a pituitary adenoma, pheochromocytoma/paraganglioma association (3PA) 14 . In individuals or kindreds presenting with 3PA, a number of mutated genes have been identified, including the succinate dehydrogenase subunit genes (SDHx); recently, mutations and intragenic deletions in MAX have also been implicated in 3PA 15 .…”
mentioning
confidence: 99%